Hepatitis Iskemik Akibat Syok Hipovolemik dengan Trombositopenia dan Disfungsi Renal: Sebuah Laporan Kasus - Muhammad Agus Putra; Syaifun Niam; Paskalis Andrew Gunawan (Universitas Pahlawan Tuanku Tambusai, 2026)
Hypovolemic shock is a condition that may lead to systemic hypoperfusion and subsequently result in multiorgan dysfunction. This case report describes a 32-year-old man who presented to the emergency department with recurrent vomiting approximately 30 times within one day, accompanied by generalized weakness, dyspnea, and abdominal pain. Physical examination revealed severe hypotension (73/44 mmHg), tachycardia, and signs of dehydration, supporting the diagnosis of hypovolemic shock. Laboratory investigations demonstrated hemoconcentration, severe thrombocytopenia (15 ×10³/µL), elevated serum creatinine and urea levels, hyperbilirubinemia, and markedly increased aminotransferase levels (AST 1088 U/L; ALT 852 U/L). Abdominal ultrasonography revealed grade 1 hepatic steatosis, cholecystitis with cholelithiasis, bilateral chronic kidney disease, and a right renal cyst. The patient received fluid resuscitation and supportive therapy, resulting in clinical and hemodynamic improvement. Serial laboratory evaluations showed an increase in platelet count to 118 ×10³/µL and a decline in AST and ALT levels to 222 U/L and 607 U/L, respectively, by the sixth day of hospitalization. This case highlights the importance of comprehensive evaluation in hypovolemic shock, as systemic hypoperfusion may lead to simultaneous dysfunction of multiple organ systems.